Study on Energy Conversion Performance and Transmission Mechanism of New Thermoelectric Materials under High Temperature Gradient - Xiao, Zhe (Scientific Journal of Technology, 2025)
This study focuses on the energy conversion performance and transmission mechanism of new thermoelectric materials under high temperature gradient. Aiming at the problems of poor thermal stability and low figure of merit (ZT) of traditional thermoelectric materials in high temperature environment, a gradient composite structure (STBT) based on SrTiO₃ with high melting point and Bi₂Te₃ with chalcogenide was designed and constructed. Continuous transition of composition is achieved through spark plasma sintering (SPS) technology, forming an interface diffusion layer with good metallurgical bonding. By combining in-situ high-temperature characterization and multiscale simulation, the electrical thermal transport operation of materials under high-temperature gradients was systematically studied in relation to their microscopic mechanisms. The results show that the STBT material has a Seebeck coefficient of -520 μ V K⁻¹ at 700 K, a power factor of 130μW m⁻¹ K⁻², and a lattice thermal conductivity reduced to 1.6 W m⁻¹ K⁻¹, ultimately achieving a ZT value of about 0.57, an order of magnitude increase compared to a single component. The performance improvement is attributed to the enhanced Seebeck coefficient due to the interface energy filtering effect, as well as the significant suppression of thermal conductivity by phonon scattering induced by thermal stress. This study provides new ideas for the design of high-temperature thermoelectric materials and demonstrates the enormous potential of gradient structures in synergistically optimizing the electrical and thermal transport performance.